Motherhood and Trauma in Wartime: A Postcolonial Feminist Reading of a Golden Age - Haris, Muhammad Naufal; Djohar, Hasnul Insani (CV. Tripe Konsultan, 2025)
This paper explored how Tahmima Anam’s A Golden Age reimagines women’s roles in wartime through the lens of postcolonial feminist theory. Centering on the character Rehana Haque, a mother navigating the 1971 Bangladesh Liberation War, the analysis highlights how motherhood, emotional labor, and trauma become politicized forms of resistance. Drawing on theoretical insights from Chandra Talpade Mohanty, Gayatri Spivak, Veena Das, and others, the study demonstrates how Rehana’s domestic and relational actions challenge dominant, masculinist narratives of nationalism. The paper argues that Rehana’s maternal identity is a site of situated agency, where caregiving and emotional endurance serve as political acts that sustain revolutionary efforts. Furthermore, the novel critiques the symbolic ideal of the “mother of the nation,” replacing it with a complex portrayal of lived experience, grief, and resilience. By foregrounding the gendered dimensions of trauma and memory, this study contributes to feminist and postcolonial literary criticism and calls for a redefinition of heroism that includes the emotional and domestic labor of women during national struggles.